Outcome predictors of acute stroke patients in need of intensive care treatment - Alonso, Angelika; Ebert, Anne; Kern, Rolf; Britsch, Simone; Hennerici, Michael G.; Fatar, Marc (Cerebrovascular diseases, 2015)
Background: The prognosis of stroke patients admitted to intensive care units (ICU) is commonly regarded to be poor. However, only limited data regarding outcome predictors are available. Patients and Methods: Out of 4,958 consecutive patients admitted to our stroke unit with the diagnosis of acute stroke, after analysis we identified 347 patients (164 male) in need of ICU management. In-hospital and post-rehabilitation mortality as well as functional outcome at discharge and after rehabilitation were analyzed. Results: Ischemic stroke was diagnosed in 252 patients (72.6%) and intracerebral hemorrhage occurred in 95 patients (27.4%). The mean age in our cohort was considerably high (70.8 years). One hundred patients were comatose at admission. The median NIHSS score at admission in the remaining patients was 12. Apart from stroke-related disturbances of consciousness (47.1%), the most common reasons for ICU treatment were cardiac (23.4%) and respiratory (12.1%) complications or interventional procedures requiring mechanical ventilation (11%). In all, 231/347 patients (66.6%) were mechanically ventilated (mean 84 h). In-hospital mortality (143/347; 41.2%) was associated with old age, poor NIHSS score at admission, intracerebral hemorrhage and mechanical ventilation (p < 0.001 in all). Further, admission to ICU because of stroke-related impairment of consciousness increased in-hospital mortality (p < 0.001). Similarly, poor outcome after rehabilitation was associated with old age (p = 0.029) and mechanical ventilation (p < 0.001). In patients ≥80 years with either intracerebral hemorrhage or need of mechanical ventilation, outcome was unfavorable in nearly any case. However, the overall post-rehabilitation outcome did not differ between patients with intracerebral hemorrhage and ischemic stroke (p = 0.275). Conclusion: The stroke population in our study was associated with an increased early mortality; however, given the same conditions, it was old with a high percentage of patients requiring mechanical ventilation. This did not result in increased in-hospital mortality rates compared to younger and less severely affected cohorts. Thus, ICU management is a life-saving initiative even among the elderly. However, the functional outcome was poor in older patients, thus limiting the benefits of ICU care in these patients.
Gesehen am 11.12.2018